Ternary positive electrode material, positive electrode sheet of lithium-ion battery and its application

By optimizing the sintering process, the cobalt compound and another compound are coated on the surface of the ternary material in one-step manner, the problem of ternary material being prone to side reactions in lithium-ion batteries is solved, and the effect of improving battery power performance and reducing gas production is achieved.

CN113921791BActive Publication Date: 2025-03-25ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111175975.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-09
Publication Date
2025-03-25
Estimated Expiration
2041-10-09

AI Technical Summary

Technical Problem

The existing ternary materials are prone to side reactions with the electrolyte in lithium-ion batteries, causing the electrolyte to decompose and produce gas, and the demand for power performance improvement has not been fully solved.

Method used

By optimizing the sintering process, the cobalt compound and another compound can be coated with nickel, cobalt, manganese ternary material in one-step manner to improve the ionic and electronic conductivity and chemical stability of the material surface.

Benefits of technology

It effectively improves the gas production problem of lithium-ion batteries and improves the power performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003295600320000171
    Figure BDA0003295600320000171
  • Figure BDA0003295600320000181
    Figure BDA0003295600320000181
Patent Text Reader

Abstract

The present invention provides a ternary positive electrode material, a lithium-ion battery positive electrode sheet and its application. The ternary positive electrode material comprises: 96-99.98wt% of a nickel-cobalt-manganese ternary material, 0.01-2wt% of a first inorganic coating material and 0.01-2wt% of a second inorganic coating material, wherein the first inorganic coating material comprises a cobalt compound. The present invention coats a cobalt compound and another compound on the surface of the ternary material, and by controlling the mass of the cobalt compound and the other compound in the ternary positive electrode material, the interaction between the two compounds can effectively improve the gas production problem of the lithium-ion battery and improve the power performance of the lithium-ion battery. By sintering once and regulating the order and temperature of adding auxiliary materials, the one-step co-coating of the ternary material with two coating auxiliary materials is achieved, the coating sintering process is improved, and the performance is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries and relates to a ternary positive electrode material, in particular to a ternary positive electrode material, a lithium-ion battery positive electrode sheet and applications thereof. Background Art

[0002] Ternary materials are widely used in high energy density power battery systems because of their high theoretical specific capacity, high reaction platform voltage, and excellent reaction kinetics. However, the widely used ternary materials are prone to side reactions with the electrolyte in the battery, causing the electrolyte to decompose and produce gas. In addition, there is a demand for improved power performance of ternary materials. The above problems can be improved by coating different substances on the surface of the ternary materials. However, the sintering temperatures required for coating different substances are often quite different, making them difficult to be compatible, making it difficult to optimize the performance of ternary materials.

[0003] How to achieve the coating of different substances in one step by improving the sintering process to obtain the optimized ternary material, thereby improving the gas production problem and improving the power performance of the battery is an urgent problem to be solved in the preparation technology of lithium-ion battery positive electrode sheets. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a ternary positive electrode material, a lithium-ion battery positive electrode sheet and applications thereof. By optimizing the sintering process, a ternary material in which a cobalt compound and another compound are co-coated in one step is prepared into a lithium-ion battery positive electrode sheet. The surface coating simultaneously improves the ionic and electronic conductivity and chemical stability of the material surface, effectively improving the gas production problem and improving the power performance of the lithium-ion battery.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a ternary positive electrode material, which comprises, by mass percentage:

[0007] Nickel-cobalt-manganese ternary material 96-99.98wt%

[0008] The first inorganic coating material 0.01-2wt%

[0009] The second inorganic coating material is 0.01-2 wt%.

[0010] The first inorganic coating material is a cobalt compound; the second inorganic coating material includes any one of M's oxides, hydroxides, oxyhydroxides, borides, fluorides, borates, carbonates, acetates, oxalates or alkoxides, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of M's oxide and hydroxide, a combination of M's oxyhydroxide and boride, a combination of M's fluoride and borate, a combination of M's acetate and oxalate, a combination of M's oxalate and alkoxide, or a combination of M's oxide, hydroxide and oxyhydroxide.

[0011] The M includes any one or a combination of at least two of B, Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Y, Zr, Nb, Mo, Ru, Sn, Sb, Ba, Hf, Ta, W, Re or Bi. Typical but non-limiting combinations include a combination of B and Mg, a combination of Al and Si, a combination of Ti and V, a combination of Mn and Fe, a combination of Ni and Cu, a combination of Zn, Sr and Y, or a combination of Zr, Nb, Mo and Ru.

[0012] In terms of mass percentage, the content of nickel, cobalt and manganese ternary material in the ternary positive electrode material is 96-99.98wt%, for example, it can be 96wt%, 96.5wt%, 97wt%, 98wt% or 99.98wt%, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 99-99.98wt%.

[0013] In terms of mass percentage, the content of the first inorganic coating material in the ternary positive electrode material is 0.01-2wt%, for example, it can be 0.01wt%, 0.1wt%, 0.5wt%, 1wt% or 2wt%, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 0.01-0.5wt%.

[0014] In terms of mass percentage, the content of the second inorganic coating material in the ternary positive electrode material is 0.01-2wt%, for example, it can be 0.01wt%, 0.1wt%, 0.5wt%, 1wt% or 2wt%, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 0.01-0.5wt%.

[0015] The sum of the mass percentages of the nickel-cobalt-manganese ternary material, the first inorganic coating material and the second inorganic coating material is 100wt%.

[0016] The present invention provides a ternary positive electrode material, on the surface of which a cobalt compound and another compound are coated. Due to the interaction between the cobalt compound and the other compound, the electronic conductivity and chemical stability of the surface of the nickel-cobalt-manganese ternary material are improved at the same time, thereby promoting the diffusion of lithium ions and reducing the occurrence of side reactions in the electrolyte. Among them, the improvement of electronic conductivity improves the power performance of the ternary positive electrode material; the improvement of chemical stability improves the gas production problem of lithium-ion batteries.

[0017] The present invention optimizes the performance of the coated material by controlling the mass of the cobalt compound and another compound in the ternary positive electrode material. When the mass percentage of the cobalt compound is greater than 2wt%, the ionic conductivity on the surface of the material decreases significantly, affecting the kinetic performance of the material; when the mass percentage of the cobalt compound is less than 0.01wt%, the coating effect is not obvious and there is no improvement in the material performance. When the mass percentage of the other compound is greater than 2wt%, the ionic conductivity on the surface of the material decreases significantly, affecting the kinetic performance of the material; when the mass percentage of the other compound is less than 0.01wt%, the coating effect is not obvious and there is no improvement in the material performance.

[0018] Preferably, the chemical formula of the nickel-cobalt-manganese ternary material is LiNi x Co y Mn 1-x-y O2, wherein 0.5≤x≤0.99, for example, x can be 0.5, 0.6, 0.7, 0.8 or 0.99; 0<y≤0.15, for example, y can be 0.01, 0.05, 0.08, 0.1, 0.12 or 0.15, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0019] Preferably, the nickel-cobalt-manganese ternary material is in a secondary spherical form and / or a single crystal form.

[0020] Preferably, the median particle size of the secondary spherical nickel-cobalt-manganese ternary material is 2 μm to 20 μm, for example, 2 μm, 5 μm, 10 μm, 15 μm or 20 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the median particle size of the single crystal nickel-cobalt-manganese ternary material is 1.5 μm to 8 μm, for example, 1.5 μm, 2 μm, 4 μm, 6 μm or 8 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the first inorganic coating material includes any one or a combination of at least two of Co3(BO3)2, CoCO3, Co(NO3)2, Co(NO3)4, CoF2, CoF3, CoO, CoO2, Co3O4, CoN, Co2N, CoH, Co3H or CoOOH. Typical but non-limiting combinations include a combination of Co3(BO3)2 and CoCO3, a combination of Co3(BO3)2 and CoF2, a combination of CoCO3 and Co3O4, a combination of CoO2 and CoOOH, a combination of Co2N and CoO, or a combination of Co3(BO3)2, CoF2 and CoO.

[0023] Preferably, the first inorganic coating material includes Co3O4 and / or CoOOH.

[0024] Preferably, the second inorganic coating material includes Al2O3 and / or H3BO3.

[0025] In a second aspect, the present invention provides a method for preparing the ternary positive electrode material according to the first aspect, the preparation method comprising:

[0026] The nickel-cobalt-manganese ternary material is subjected to sintering at a high temperature, and when the temperature is raised to a first temperature rising stage, the first inorganic coating material is mixed with the nickel-cobalt-manganese ternary material to obtain a mixed material; and

[0027] When the temperature is raised to the second temperature rising stage, the second inorganic coating material is mixed with the mixed material, and the temperature is continued to be raised and sintered to obtain the ternary positive electrode material.

[0028] Since different substances often require greatly different temperatures during the coating process, the preparation method provided by the present invention is different from the step-by-step coating method in the prior art. By optimizing the sintering process, the nickel-cobalt-manganese ternary material is sintered only once. By regulating the heating rate and the order of adding inorganic coating substances in different sintering temperature sections, a one-step coating of multiple substances is achieved to prepare a ternary positive electrode material.

[0029] Preferably, the heating rate of the temperature-raising sintering is 1°C / min to 6°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or 6°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the temperature of the first heating section is 200°C to 500°C, for example, it can be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the temperature of the second heating stage is 550°C to 650°C, for example, 550°C, 570°C, 600°C, 620°C or 650°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the terminal sintering temperature of the elevated temperature sintering is 600°C to 650°C, for example, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the sintering time after heating to the final sintering temperature is 2 to 20 hours, for example, 2 hours, 5 hours, 10 hours, 15 hours or 20 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] As a preferred technical solution of the preparation method described in the second aspect of the present invention, the preparation method comprises:

[0035] Obtaining the mixed material comprises: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 2° C. / min to 6° C. / min, and when the temperature is raised to 200° C. to 400° C., mixing the first inorganic coating material with the nickel-cobalt-manganese ternary material to obtain the mixed material;

[0036] The method of obtaining the ternary positive electrode material comprises: when the temperature is raised to 700° C. to 800° C., mixing the second inorganic coating material with the mixed material, continuing to raise the temperature to 900-950° C., and sintering for 2 h to 20 h to obtain the ternary positive electrode material.

[0037] In a third aspect, the present invention provides a positive electrode sheet for a lithium-ion battery, wherein the positive electrode sheet for a lithium-ion battery comprises the ternary positive electrode material described in the first aspect of the present invention.

[0038] Preferably, the lithium-ion battery positive electrode plate further includes a conductive agent and a colloidal binder.

[0039] Preferably, the mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder in the lithium ion battery positive electrode sheet is (90-99):(0.5-3.5):(20-43), for example, it can be 90:0.5:20, 99:3.5:43, 90:3.5:20, 99:0.5:43 or 99:3.5:20, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In a fourth aspect, the present invention provides an application of the lithium-ion battery positive electrode sheet as described in the third aspect, wherein the lithium-ion battery positive electrode sheet is used in a lithium-ion battery.

[0041] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The present invention coats the surface of the ternary material with two inorganic coating materials, a cobalt compound and another compound. By controlling the masses of the cobalt compound and the other compound in the ternary positive electrode material, the interaction between the two compounds is achieved, which can effectively improve the gas production problem of the lithium-ion battery and enhance the power performance of the lithium-ion battery.

[0044] (2) The present invention realizes one-step coating of two coating auxiliary materials on ternary materials by sintering once and regulating the order and temperature of adding auxiliary materials, improves the coating sintering process, and optimizes the performance of ternary positive electrode materials. DETAILED DESCRIPTION

[0045] Among the disclosed technical solutions, one technical solution discloses an Al2O3-coated nickel-cobalt-aluminum ternary lithium-ion battery positive electrode material, comprising a nickel-cobalt-aluminum lithium oxide material and Al2O3 coated on the surface of the nickel-cobalt-aluminum lithium oxide material. The chemical formula of the Al2O3-coated nickel-cobalt-aluminum ternary lithium-ion battery positive electrode material is (Li a Ni 1-x-y Co x Al y ) 1-b Al b O2, x>0, y>0, 1-xy>0, 1≤a≤1.1, 0<b≤0.02. The preparation method of the material is to firstly prepare the ternary positive electrode material precursor Ni 1-x- y Co x Al y (OH) 2+y Sintering; then adding the sintered product to a lithium source for sintering; and finally adding a coating material Al2O3 for sintering to obtain a target product. The Al2O3-coated nickel-cobalt-aluminum ternary lithium-ion battery positive electrode material has excellent cycle performance.

[0046] Another technical solution discloses a preparation method for a positive electrode material for a lithium-ion battery, specifically a preparation method for a ternary positive electrode material coated with Co and Ti by ball milling. The method comprises the following steps: Step 1, three-dimensionally mechanically mixing a 523-type ternary precursor with battery-grade lithium carbonate, then sintering at 600-700°C in an air-permeable sintering furnace, grinding and crushing after cooling to obtain a 523 ternary positive electrode material; Step 2, mixing the 523 ternary positive electrode material with cobalt oxide, battery-grade lithium carbonate, and analytical grade TiO2 additive in a high-energy ball mill, taking out the mixed sample and washing it with distilled water, taking out the sample after sintering and grinding it to obtain a finished product. The preparation method can coat the surface of the ternary material with LiCoO2, and use Ti to modify the LiCoO2 part, which can effectively improve the capacity retention rate of the ternary positive electrode material for multiple cycles.

[0047] The ternary positive electrode material in the above technical solution has a gas generation problem, and the prepared lithium-ion battery has low power.

[0048] In order to solve the above technical problems, the present invention provides a ternary positive electrode material, a lithium-ion battery positive electrode sheet and applications thereof. By optimizing the sintering process, a ternary material co-coated with a cobalt compound and another compound in one step is prepared into a lithium-ion battery positive electrode sheet. The surface coating simultaneously improves the ionic and electronic conductivity and chemical stability of the material surface, effectively improving the gas production problem and improving the power performance of the lithium-ion battery.

[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0050] Example 1

[0051] This embodiment provides a ternary positive electrode material, which includes, by mass percentage, the following:

[0052] Nickel-cobalt-manganese ternary material 99.6wt%

[0053] CoOOH 0.2wt%

[0054] Al2O3 0.2wt%.

[0055] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.55 Co 0.15 Mn 0.3 O2, median particle size is 10μm.

[0056] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 4°C / min, and when the temperature is raised to 350°C, mixing CoOOH with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 600°C, mixing Al2O3 with the mixture, continuing to heat to 630°C, and sintering for 10 hours to obtain the ternary positive electrode material.

[0057] This embodiment provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 97.5:1.5:41.

[0058] Example 2

[0059] This embodiment provides a ternary positive electrode material, which includes, by mass percentage, the following:

[0060] Nickel-cobalt-manganese ternary material 99wt%

[0061] Co2O3 0.5wt%

[0062] H3BO3 0.5wt%.

[0063] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.5 Co 0.15 Mn 0.35 O2, median particle size is 20μm.

[0064] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 2°C / min, and when the temperature is raised to 400°C, mixing Co2O3 with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 625°C, mixing H3BO3 with the mixture, continuing to heat to 640°C, and sintering for 15 hours to obtain the ternary positive electrode material.

[0065] This embodiment provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 99:1.5:41.

[0066] Example 3

[0067] This embodiment provides a ternary positive electrode material, which includes, by mass percentage, the following:

[0068] Nickel-cobalt-manganese ternary material 99.98wt%

[0069] CoCO3 0.01wt%

[0070] V2O5 0.01wt%.

[0071] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.5 Co 0.15 Mn 0.35 O2, median particle size is 2μm.

[0072] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 5°C / min, and when the temperature is raised to 300°C, mixing CoCO3 with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 575°C, mixing Y2O5 with the mixture, continuing to heat to 620°C, and sintering for 5 hours to obtain the ternary positive electrode material.

[0073] This embodiment provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 90:3.5:20.

[0074] Example 4

[0075] This embodiment provides a ternary positive electrode material, except that the nickel-cobalt-manganese ternary material is a single crystal LiNi 0.5 Co 0.15 Mn 0.35 O2, except that the median particle size is 5 μm, the rest is the same as Example 1.

[0076] Example 5

[0077] This embodiment provides a ternary positive electrode material, which includes, by mass percentage, the following:

[0078] Nickel-cobalt-manganese ternary material 98wt%

[0079] CoF3 1wt%

[0080] Y2O3 1wt%.

[0081] The nickel-cobalt-manganese ternary material is a single crystal LiNi 0.5 Co 0.15 Mn 0.35 O2, median particle size is 1.5μm.

[0082] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 1°C / min, and when the temperature is raised to 500°C, mixing CoF3 with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 650°C, mixing Y2O3 with the mixture, continuing to heat to 650°C, and sintering for 20 hours to obtain the ternary positive electrode material.

[0083] This embodiment provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 99:0.5:43.

[0084] Example 6

[0085] This embodiment provides a ternary positive electrode material, which includes, by mass percentage, the following:

[0086] Nickel-cobalt-manganese ternary material 96wt%

[0087] Co2N 2wt%

[0088] Mo(NO3)3 2wt%.

[0089] The nickel-cobalt-manganese ternary material is a single crystal LiNi 0.55 Co 0.15 Mn 0.3 O2, median particle size is 8μm.

[0090] The preparation method of the ternary positive electrode material includes the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 6°C / min, and when the temperature is raised to 200°C, mixing Co2N with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 550°C, mixing Mo(NO3)3 with the mixture, continuing to heat to 600°C, and sintering for 2h to obtain the ternary positive electrode material.

[0091] This embodiment provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 99:1.5:35.

[0092] Example 7

[0093] This embodiment provides a ternary positive electrode material, except that the chemical formula of the nickel-cobalt-manganese ternary material is LiNi 0.5 Co 0.15 Mn0.35 O2, including a single crystal form and a secondary spherical form in a mass ratio of 1:1, the median particle size of the single crystal form is 5μm, and the median particle size of the secondary spherical form is 10μm, and the rest is the same as Example 1.

[0094] Example 8

[0095] This embodiment provides a ternary positive electrode material, except that the chemical composition of the nickel-cobalt-manganese ternary material is LiNi 0.99 Co 0.005 Mn 0.005 Except for O2, the rest are the same as in Example 1.

[0096] Example 9

[0097] This embodiment provides a ternary positive electrode material, except that the chemical composition of the nickel-cobalt-manganese ternary material is LiNi 0.6 Co 0.15 Mn 0.25 Except for O2, the rest are the same as in Example 1.

[0098] Example 10

[0099] This embodiment provides a ternary positive electrode material, except that the chemical composition of the nickel-cobalt-manganese ternary material is LiNi 0.8 Co 0.1 Mn 0.1 Except for O2, the rest are the same as in Example 1.

[0100] Embodiment 11

[0101] This embodiment provides a ternary positive electrode material. Except for sintering at a heating rate of 1° C. / min, the remaining process steps and material contents are the same as those in Embodiment 1.

[0102] Example 12

[0103] This embodiment provides a ternary positive electrode material. Except for sintering at a heating rate of 8° C. / min, the remaining process steps and material contents are the same as those in Embodiment 1.

[0104] Embodiment 13

[0105] This embodiment provides a ternary positive electrode material. Except that the temperature for mixing CoOOH and the nickel-cobalt-manganese ternary material is 160° C., the remaining process steps and material contents are the same as those in Embodiment 1.

[0106] Embodiment 14

[0107] This embodiment provides a ternary positive electrode material. Except that the temperature for mixing CoOOH and the nickel-cobalt-manganese ternary material is 450° C., the remaining process steps and material contents are the same as those in Embodiment 1.

[0108] Embodiment 15

[0109] This embodiment provides a ternary positive electrode material. Except that the temperature for mixing Al2O3 and the mixed material is 660°C, the remaining process steps and material contents are the same as those in Embodiment 1.

[0110] Example 16

[0111] This embodiment provides a ternary positive electrode material. Except that the temperature for mixing Al2O3 and the mixed material is 850°C, the remaining process steps and material contents are the same as those in Embodiment 1.

[0112] Embodiment 17

[0113] This embodiment provides a ternary positive electrode material. Except that the preparation method of the ternary positive electrode material is different from that in Embodiment 1, the contents of other materials are the same as those in Embodiment 1.

[0114] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 4°C / min, and when the temperature is raised to 300°C, mixing Al2O3 with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 750°C, mixing CoOOH with the mixture, continuing to heat to 920°C, and sintering for 10 hours to obtain the ternary positive electrode material.

[0115] Comparative Example 1

[0116] This comparative example provides a ternary positive electrode material, which comprises, by mass percentage:

[0117] Nickel-cobalt-manganese ternary material 97.3wt%

[0118] CoOOH 2.5wt%

[0119] Al2O3 0.2wt%.

[0120] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.55 Co 0.15 Mn 0.3 O2, median particle size is 10μm.

[0121] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 4°C / min, and when the temperature is raised to 350°C, mixing CoOOH with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 600°C, mixing Al2O3 with the mixture, continuing to heat to 630°C, and sintering for 10 hours to obtain the ternary positive electrode material.

[0122] This comparative example provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 97.5:1.5:41.

[0123] Comparative Example 2

[0124] This comparative example provides a ternary positive electrode material, which comprises, by mass percentage:

[0125] Nickel-cobalt-manganese ternary material 99.795wt%

[0126] CoOOH 0.005wt%

[0127] Al2O3 0.2wt%.

[0128] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.55 Co 0.15 Mn 0.3 O2, median particle size is 10μm.

[0129] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 4°C / min, and when the temperature is raised to 350°C, mixing CoOOH with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 600°C, mixing Al2O3 with the mixture, continuing to heat to 630°C, and sintering for 10 hours to obtain the ternary positive electrode material.

[0130] This comparative example provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 97.5:1.5:41.

[0131] Comparative Example 3

[0132] This comparative example provides a ternary positive electrode material, which comprises, by mass percentage:

[0133] Nickel-cobalt-manganese ternary material 97.3wt%

[0134] CoOOH 0.2wt%

[0135] Al2O3 2.5wt%.

[0136] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.55 Co0.15 Mn 0.3 O2, median particle size is 10μm.

[0137] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 4°C / min, and when the temperature is raised to 350°C, mixing CoOOH with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 600°C, mixing Al2O3 with the mixture, continuing to heat to 630°C, and sintering for 10 hours to obtain the ternary positive electrode material.

[0138] This comparative example provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 97.5:1.5:41.

[0139] Comparative Example 4

[0140] This comparative example provides a ternary positive electrode material, which comprises, by mass percentage:

[0141] Nickel-cobalt-manganese ternary material 99.795wt%

[0142] CoOOH 0.2wt%

[0143] Al2O3 0.005wt%.

[0144] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.55 Co 0.15 Mn 0.3 O2, median particle size is 10μm.

[0145] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 4°C / min, and when the temperature is raised to 350°C, mixing CoOOH with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 600°C, mixing Al2O3 with the mixture, continuing to heat to 630°C, and sintering for 10 hours to obtain the ternary positive electrode material.

[0146] This comparative example provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 97.5:1.5:41.

[0147] Comparative Example 5

[0148] This comparative example provides a ternary positive electrode material, which comprises, by mass percentage:

[0149] Nickel-cobalt-manganese ternary material 99.6wt%

[0150] CoOOH 0.4wt%

[0151] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.55 Co 0.15 Mn 0.3 O2, median particle size is 10μm.

[0152] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 4°C / min, and when the temperature reaches 350°C, mixing CoOOH with the nickel-cobalt-manganese ternary material, continuing to heat to 630°C, and sintering for 10 hours to obtain the ternary positive electrode material.

[0153] This comparative example provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 97.5:1.5:41.

[0154] Comparative Example 6

[0155] This comparative example provides a ternary positive electrode material, which comprises, by mass percentage:

[0156] Nickel-cobalt-manganese ternary material 99.6wt%

[0157] Al2O3 0.4wt%.

[0158] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.55 Co 0.15 Mn 0.3 O2, median particle size is 10μm.

[0159] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 4°C / min, and when the temperature reaches 600°C, mixing Al2O3 and the nickel-cobalt-manganese ternary material, continuing to heat to 630°C, and sintering for 10 hours to obtain the ternary positive electrode material.

[0160] This comparative example provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 97.5:1.5:41.

[0161] Comparative Example 7

[0162] This comparative example provides a ternary positive electrode material, which comprises, by mass percentage:

[0163] Nickel-cobalt-manganese ternary material 99.6wt%

[0164] H3BO3 0.2wt%

[0165] Al2O3 0.2wt%.

[0166] The nickel-cobalt-manganese ternary material is a secondary spherical LiNi 0.55 Co 0.15 Mn 0.3 O2, median particle size is 10μm.

[0167] The preparation method of the ternary positive electrode material comprises the following steps: heating and sintering the nickel-cobalt-manganese ternary material at a heating rate of 4°C / min, and when the temperature is raised to 350°C, mixing H3BO3 with the nickel-cobalt-manganese ternary material to obtain a mixture; when the temperature is raised to 600°C, mixing Al2O3 with the mixture, continuing to heat to 630°C, and sintering for 10 hours to obtain the ternary positive electrode material.

[0168] This comparative example provides a lithium-ion battery positive electrode sheet, which includes the ternary positive electrode material, conductive carbon black and conductive carbon tubes used as conductive agents, and polyvinylidene fluoride and nitrogen-methyl pyrrolidone used as colloidal binders. The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder is 97.5:1.5:41.

[0169] The lithium-ion battery positive plates prepared in Examples 1-17 and Comparative Examples 1-7 were assembled into 1Ah soft-pack batteries according to GB31241-2014. At 25°C, the battery was charged to a voltage of 4.3V at a rate of 0.33C, and discharged to 2.8V at 0.33C to obtain a capacity C0. The state of charge of the battery was then adjusted to 70% SOC, and the battery was discharged at a current density of 4C for 30s. The voltage difference before and after discharge divided by the current density is the DC resistance (DCR) of the battery at the state of charge (SOC). The DCR values ​​of 50% SOC and 20% SOC can be measured in this way. After that, the battery was placed in a -20°C constant temperature oven, and charged and discharged twice at a current density of 0.33C in a voltage window of 2.8V-4.3V, and the second discharge capacity C1 was recorded. C1 / C0 is the low-temperature capacity retention rate of the battery. At the same time, the DCR value of the battery was tested at a temperature of -20°C. In addition, the test battery with 100% SOC was stored in a 60°C environment, and the battery volume was measured every 7 days and recharged to 100% SOC. The rate of change of the battery volume is the measured gas generation rate. The results are shown in Table 1.

[0170] Table 1

[0171]

[0172]

[0173]

[0174] The following conclusions can be drawn from the data in Table 1:

[0175] (1) It can be seen from Examples 1-10 that the surface of the ternary positive electrode material provided by the present invention is coated with cobalt and another compound and is obtained by a single sintering coating. The lithium ion battery positive electrode sheet prepared in this way is assembled into a lithium ion battery with a high low-temperature capacity retention rate and a low DC resistance value, and has a low gas generation rate.

[0176] (2) Comparing the results of Examples 11 and 12 with those of Example 1, it can be seen that when the heating rate for preparing the ternary positive electrode material is greater than 6°C / min or less than 2°C / min, the lithium ion battery positive electrode sheet prepared thereby has a low low temperature capacity retention rate, a high DC resistance value, and a gas production problem when assembled into a lithium ion battery. This indicates that the heating rate provided by the present invention is helpful to coat cobalt and another compound on the surface of the ternary positive electrode material, and obtain the result by sintering and coating once, so that the lithium ion battery positive electrode sheet prepared thereby has a high low temperature capacity retention rate and a low DC resistance value when assembled into a lithium ion battery, and has a low gas production rate.

[0177] (3) Comparing the results of Examples 13 and 14 with those of Example 1, it can be seen that when the temperature for adding the inorganic coating material Co-X is greater than 400°C or less than 200°C, the lithium ion battery positive electrode sheet thus prepared is assembled into a lithium ion battery with a low low temperature capacity retention rate, a high DC resistance value, and a gas generation problem. This indicates that the temperature for adding the inorganic coating material Co-X provided by the present invention is conducive to coating cobalt and another compound on the surface of the ternary positive electrode material, and obtaining the coating by one sintering, so that the lithium ion battery positive electrode sheet thus prepared is assembled into a lithium ion battery with a high low temperature capacity retention rate and a low DC resistance value, and has a low gas generation rate.

[0178] (4) Comparing the results of Examples 15 and 16 with those of Example 1, it can be seen that when the temperature of adding the inorganic coating material MY is greater than 800°C or less than 700°C, the lithium ion battery positive electrode sheet thus prepared is assembled into a lithium ion battery with a low low temperature capacity retention rate, a high DC resistance value, and a gas generation problem. This indicates that the temperature of adding the inorganic coating material MY provided by the present invention is conducive to coating cobalt and another compound on the surface of the ternary positive electrode material, and obtaining the coating by one sintering, so that the lithium ion battery positive electrode sheet thus prepared is assembled into a lithium ion battery with a high low temperature capacity retention rate and a low DC resistance value, and has a low gas generation rate.

[0179] (5) Comparison of the results of Example 17 with those of Example 1 shows that when the order of adding the inorganic coating material Co-X and the inorganic coating material MY is changed, the lithium ion battery positive electrode sheet thus prepared is assembled into a lithium ion battery with a low low temperature capacity retention rate, a high DC resistance value, and a gas generation problem. This indicates that the order of adding the inorganic coating material Co-X and the inorganic coating material MY provided by the present invention is conducive to coating cobalt and another compound on the surface of the ternary positive electrode material, and obtaining the coating by one sintering, so that the lithium ion battery positive electrode sheet thus prepared is assembled into a lithium ion battery with a high low temperature capacity retention rate and a low DC resistance value, and a low gas generation rate.

[0180] (6) Comparison of the results of Comparative Examples 1 and 2 with those of Example 1 shows that when the mass percentage of the inorganic coating material Co-X is greater than 2wt%, or less than 0.01wt%, the lithium ion battery positive electrode sheet prepared therefrom has a low low temperature capacity retention rate, a high DC resistance value, and a gas generation problem when assembled into a lithium ion battery. This indicates that the mass percentage content of the inorganic coating material Co-X provided by the present invention is conducive to coating cobalt and another compound on the surface of the ternary positive electrode material, and is obtained by a single sintering coating, so that the lithium ion battery positive electrode sheet prepared therefrom has a high low temperature capacity retention rate and a low DC resistance value when assembled into a lithium ion battery, and has a low gas generation rate.

[0181] (7) Comparison of the results of Comparative Examples 3 and 4 with those of Example 1 shows that when the mass percentage of the inorganic coating material MY is greater than 2wt%, or less than 0.01wt%, the lithium ion battery positive electrode sheet prepared therefrom has a low low temperature capacity retention rate, a high DC resistance value, and a gas generation problem when assembled into a lithium ion battery. This indicates that the mass percentage content of the inorganic coating material MY provided by the present invention is conducive to coating cobalt and another compound on the surface of the ternary positive electrode material, and is obtained by a single sintering coating, so that the lithium ion battery positive electrode sheet prepared therefrom has a high low temperature capacity retention rate and a low DC resistance value when assembled into a lithium ion battery, and has a low gas generation rate.

[0182] (7) Comparison of the results of Comparative Examples 5 and 6 with those of Example 1 shows that when only one inorganic coating material is added, the lithium ion battery positive electrode sheet thus prepared has a low low temperature capacity retention rate, a high DC resistance value, and a gas generation problem when assembled into a lithium ion battery. This indicates that the two inorganic coating materials provided by the present invention are helpful for coating cobalt and another compound on the surface of the ternary positive electrode material, and are obtained by sintering and coating once, so that the lithium ion battery positive electrode sheet thus prepared has a high low temperature capacity retention rate and a low DC resistance value when assembled into a lithium ion battery, and has a low gas generation rate.

[0183] (8) Comparison of the results of Comparative Example 7 with those of Example 1 shows that when the first inorganic coating material is not a compound containing cobalt, the lithium ion battery positive electrode sheet prepared therefrom has a low low temperature capacity retention rate and a high DC resistance value when assembled into a lithium ion battery, and has a gas generation problem. This indicates that the inorganic coating material Co-X provided by the present invention is helpful to coat cobalt and another compound on the surface of the ternary positive electrode material, and is obtained by a single sintering coating, so that the lithium ion battery positive electrode sheet prepared therefrom has a high low temperature capacity retention rate and a low DC resistance value when assembled into a lithium ion battery, and has a low gas generation rate.

[0184] In summary, the surface of the ternary positive electrode material provided by the present invention is coated with cobalt and another compound and is obtained by a single sintering coating. The lithium ion battery positive electrode sheet prepared in this way is assembled into a lithium ion battery with high low-temperature capacity retention rate and low DC resistance value, and has a low gas production rate.

[0185] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A ternary positive electrode material, characterized in that: In terms of mass percentage, the ternary cathode material comprises: Nickel-cobalt-manganese ternary material 96-99.98wt% The first inorganic coating material 0.01-2wt% The second inorganic coating material 0.01-2wt%, The first inorganic coating material includes a cobalt compound; the second inorganic coating material includes any one of oxides, hydroxides, oxyhydroxides, borides, fluorides, borates, carbonates, acetates, oxalates or alkoxides of M, or a combination of at least two thereof; the M includes any one of Mg, Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Y, Zr, Nb, Mo, Ru, Sn, Sb, Ba, Hf, Ta, W, Re or Bi, or a combination of at least two thereof; The nickel-cobalt-manganese ternary material is in the form of a secondary sphere and / or a single crystal; The ternary positive electrode material is prepared by the following preparation method, which comprises the following steps: The nickel-cobalt-manganese ternary material is sintered at a high temperature. When the temperature is raised to a first temperature rising stage of 200°C to 500°C, the first inorganic coating material is mixed with the nickel-cobalt-manganese ternary material to obtain a mixture. When the temperature is raised to a second temperature rising stage of 550°C to 650°C, the second inorganic coating material is mixed with the mixture, and the temperature is continued to be raised to 600°C to 650°C for sintering to obtain the ternary positive electrode material.

2. The ternary cathode material according to claim 1, characterized in that: In terms of mass percentage, the ternary cathode material comprises: Nickel-cobalt-manganese ternary material 99-99.98wt% The first inorganic coating material 0.01-0.5wt% The second inorganic coating material is 0.01-0.5wt%.

3. The ternary cathode material according to claim 1, characterized in that: The chemical formula of the nickel-cobalt-manganese ternary material is LiNi x Co y Mn 1-x-y O2, where 0.5≤x≤0.99, 0<y≤0.

15.

4. The ternary cathode material according to claim 1, characterized in that: The median particle size of the secondary spherical nickel-cobalt-manganese ternary material is 2 μm to 20 μm.

5. The ternary cathode material according to claim 1, characterized in that: The median particle size of the single crystal nickel-cobalt-manganese ternary material is 1.5 μm to 8 μm.

6. The ternary cathode material according to claim 1, characterized in that: The first inorganic coating material includes any one of Co3(BO3)2, CoCO3, Co(NO3)2, Co(NO3)4, CoF2, CoF3, CoO, CoO2, Co3O4, CoN, Co2N, CoH, Co3H or CoOOH, or a combination of at least two of them.

7. The ternary cathode material according to claim 6, characterized in that: The first inorganic coating material includes Co3O4 and / or CoOOH.

8. The ternary cathode material according to claim 1, characterized in that: The second inorganic coating material includes Al2O3.

9. A method for preparing a ternary positive electrode material according to any one of claims 1 to 8, characterized in that: The preparation method comprises: The nickel-cobalt-manganese ternary material is subjected to sintering at a high temperature, and when the temperature is raised to a first temperature rising stage of 200° C. to 500° C., the first inorganic coating material is mixed with the nickel-cobalt-manganese ternary material to obtain a mixed material; and When the temperature is raised to the second temperature rising stage of 550° C. to 650° C., the second inorganic coating material is mixed with the mixed material, and the temperature is further raised to 600° C. to 650° C. for sintering to obtain the ternary positive electrode material.

10. The preparation method according to claim 9, characterized in that: The heating rate of the heating sintering is 1°C / min to 6°C / min.

11. The preparation method according to claim 9, characterized in that: The sintering time after heating to the final sintering temperature is 2h to 20h.

12. A positive electrode sheet for a lithium-ion battery, characterized in that: The lithium-ion battery positive electrode sheet comprises the ternary positive electrode material according to any one of claims 1-8.

13. The lithium-ion battery positive electrode sheet according to claim 12, characterized in that: The lithium ion battery positive electrode sheet also includes a conductive agent and a colloidal binder.

14. The lithium-ion battery positive electrode sheet according to claim 12, characterized in that: The mass ratio of the ternary positive electrode material, the conductive agent and the colloidal binder in the positive electrode sheet of the lithium ion battery is (90-99):(0.5-3.5):(20-43).

15. An application of a lithium-ion battery positive electrode sheet according to any one of claims 12 to 14, characterized in that: The lithium ion battery positive electrode sheet is used for lithium ion batteries.

Citation Information

Patent Citations

  • Co / B co-cladded nickel cobalt manganese lithium ion cathode material, and preparation method thereof

    CN108807926A

  • Nickel-cobalt-lithium manganate ternary cathode material and preparation method thereof

    CN110474026A